Global mobility of blue-collar workforce: Sourcing talent from outside the EU - Snygg, Noel (My University, 2021)
Aging demographics and rising educational levels in Europe are making EU-based companies increasingly reliant on immigration to meet talent needs. This is especially true in manufacturing industries that are reliant on operative-level blue-collar talent. However, non-EU talent sourcing is much more complex and challenging compared to intra-EU or domestic talent sourcing due to higher levels of regulation, increased bureaucracy, and other challenges. Furthermore, previous research on global workforce mobility and international talent sourcing has placed a heavy emphasis on the mobility of managers, experts, and academics, leaving the blue-collar side of the equation relatively unexplored. This thesis aims to shed light on non-EU talent sourcing from the blue-collar point of view by answering the research question “How can Valmet Automotive conduct blue-collar talent sourcing from outside the EU?”. The study was conducted as a qualitative case study, treating the process of non-EU blue-collar talent sourcing as a “bounded system”. Data was gathered via expert interviews from industrial companies, talent sourcing partner companies and institutional entities. The interview data was supplemented by secondary data gathered from public data sources, such as different databases. Results of the study indicated that non-EU blue-collar talent sourcing is still a relatively unexplored opportunity among industrial companies. Based on the data gathered, Valmet Automotive could develop their non-EU blue-collar talent sourcing via long-term co-operation in institutional initiatives, benchmarking processes and methods from talent sourcing partners or by developing internal competences through the expansion of the HR function and recruitment process development.

Ikääntyvät väestörakenteet sekä nousevat koulutustasot Euroopassa tekevät EU:ssa toimivista valmistavan teollisuuden yrityksistä entistä riippuvaisempia maahanmuutosta työvoimatarpeiden tyydyttämiseksi. EU:n ulkopuolinen työvoiman hankinta on kuitenkin paljon monimutkaisempaa ja haastavampaa kuin EU:n sisäinen tai kotimainen työvoiman hankinta tiukemman sääntelyn, lisääntyvän byrokratian ja muiden haasteiden vuoksi. Aikaisempi tutkimus liittyen globaaliin työvoiman liikkuvuuteen ja kansainväliseen työvoiman hankintaan on keskittynyt johtajien, asiantuntijoiden ja akateemikkojen liikkuvuuteen, jättäen yhtälön sinikauluspuolen vähemmälle huomiolle. Tämä tutkielma pyrkii avaamaan EU:n ulkopuolista työvoiman hankintaa sinikauluskontekstissa vastaamalla tutkimuskysymykseen ”Miten Valmet Automotive voi toteuttaa EU-alueen ulkopuolista sinikaulustyövoiman hankintaa?”. Tutkielma toteutettiin kvalitatiivisena tapaustutkimuksena, käsitellen EU-alueen ulkopuolista sinikaulustyövoiman hankintaa ”rajattuna systeeminä”. Data kerättiin asiantuntijahaastattelujen avulla teollisuusyrityksistä, henkilöstöpalveluyrityksistä sekä instituutiosta. Haastatteludatan täydentämiseksi kerättiin sekundääridataa erilaisista julkisista tietolähteistä kuten tietokannoista. Tulokset osoittivat EU-alueen ulkopuolisen sinikaulustyövoiman hankinnan olevan suhteellisen tutkimaton aihe teollisuusyritysten parissa. Kerätyn datan perusteella Valmet Automotive voisi kehittää EU-alueen ulkopuolista sinikaulustyövoiman hankintaa pitkäaikaisella yhteistyöllä institutionaalisissa hankkeissa, omaksumalla parhaita käytäntöjä henkilöstöpalveluyrityksiltä tai kehittämällä yrityksen sisäistä osaamista laajentamalla HR-funktiota ja kehittämällä rekrytointiprosesseja.
Keywords: International talent sourcing, industry, blue-collar